The ecosystem services of the elements of the fortress landscape in Warsaw fortress in the context of a contemporary city - Justyna Jastrzębska; Ewa Zaraś; Jakub Botwina (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The contemporary elements of fortress landscape in the city can be an incredibly important component of the cultural landscape, green infrastructure system, and the natural system of the city (NSC). Due to their specific organization in space, their role in city structures is linked to providing ecosystem services in all aspects. Unfortunately, very often elements of the fortress landscape are destroyed due to improperly chosen patterns of use. The presented article focuses on the analysis of the functioning of fortress objects in terms of ecosystem services, with a primary emphasis on their functioning in the city’s natural system and their role as tourist attractions, using the example of Warsaw Fortress.